Why Nations Fail, by Daron Acemoglu and James Robinson (Meridiano 47 - Journal of Global Studies, 2017)
ACEMOGLU, Daron; ROBINSON, James. Why Nations Fail: The Origins of Power, Prosperity and Poverty. New York: Crown, 2012, 544 p.